Pengembangan Media Pembelajaran Bahasa melalui Transformasi Digital Berbasis E-Learning - Arozatulo Bawamenewi; Yaredi Waruwu (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2023)
The aim of this research is to implement e-learning applications to improve the quality of learning and increase student enthusiasm the learning process. Learning quality standards that are more consistent with the e-learning system are absolutely necessary to anticipate current developments with the support of information technology in the era of industry 4.0 and society 5.0. This research was conducted qualitatively with a descriptive research approach. Research subjects of lecturers and students. All selected subjects can be sampled because of the saturated sampling technique used. Data collection techniques include observation, interviews, and documentation of e-learning media via the Nias University website. The research instrument was modified by the researcher, namely the use of e-learning application tools, online learning media, and the benefits of e-learning in language learning. The research results show that the implementation of e-learning can be applied in the offline learning process with several benefits, namely flexible access, material selection, self-paced learning, interactive, extensive resource access, cost efficiency, diversified learning, learning track record, learning environment, reducing geographical barriers, and being able to provide opportunities for collaboration between students from geographic locations to understand in depth the advice from various sources.